the user's voice in the strategic planning of public libraries using Quality Function Deployment (QFD) - Romo - González, José Refugio (2018)
Strategic planning has traditionally worked by listening to the voice of managers. In addition to the study of its environments and functional processes, this initiative considers it fundamental to listen to the voice of the user, when assessing that they are the ones that truly face the conditions of the quality of library services. for this reason, the results of a study of users are taken as a reference, where the tool of Deployment of the Quality Function (QFD) was applied in public libraries of the municipality of Chihuahua, Mexico. This allowed to identify that the strategic planning of libraries in an integral administrative system can be sustained in the management of the quality and in the table of performance indicators, whose implantation will be able to be developed under a cycle of design, control, improvement and innovation to reach harmonic and systematic objectives.